Isolation, Characterization of Banana Starch and its Evaluation as a Disintegrating Agent in Dispersible Lornoxicam Tablet - Puri, Abhijeet V.; Gokhale, Vrushali N. (Drug Delivery Letters, 2022)
Objective: The present study was designed to isolate, characterize, formulate, and evaluate the disintegration properties of banana starch in dispersible Lornoxicam tablet formulation. Methods: The alkaline extraction method used sodium hydroxide as a lye solution to isolate starch from unripe banana fruit. Starch was subjected to characterization for physicochemical properties, viscosity and flow properties, Fourier-transform infrared spectroscopy (FTIR) scanning electron microscopy (SEM), differential scanning calorimetry (DSC) and X-ray crystallography (XRD) study. Flow properties of starch were determined as per the standard procedure. Tablets were formulated by a wet granulation method using starch as a disintegrant, and the in-vitro release characteristic of the prepared tablets was analyzed. Different concentrations of isolated starch were studied for disintegrating properties compared to corn starch. Results: Studies indicate that starch obtained is qualitatively and quantitatively comparable to corn starch. SEM, FTIR, DSC and XRD data confirmed the polysaccharide nature of the starch. The physicochemical properties of starch passed the prescribed evaluation tests for tablets. These tablets also confirmed the disintegration and dissolution specifications as per Indian Pharmacopoeia. Conclusion: From the above study, it can be concluded that starch obtained from banana shows qualitatively and quantitatively good disintegration characteristics compared to corn starch. These tablets also confirmed a significant degree of dissolution as per the standards. Evaluations also specified that banana starch possesses acceptable disintegrating characteristics compared to corn starch and can be used as a disintegrant in tablet formulation.
Keywords: Starch